2009
DOI: 10.2139/ssrn.1476461
|View full text |Cite
|
Sign up to set email alerts
|

Who Wants to Deliberate - and Why?

Abstract: Interest in deliberative theories of democracy has grown tremendously among political theorists over the last twenty years. Many scholars in political behavior, however, are skeptical that it is a practically viable theory, even on its own terms. They argue (inter alia) that most people dislike politics, and that deliberative initiatives would amount to a paternalistic imposition. Using two large, representative samples investigating people's hypothetical willingness to deliberate and their actual behavior in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
198
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(218 citation statements)
references
References 18 publications
10
198
1
9
Order By: Relevance
“…En Estados Unidos, Neblo et al (2010) observan la existencia de profundas actitudes prodeliberativas entre los americanos frente a la tradicional participación electoral. En Europa, sin embargo, diversos trabajos han explorado esta tesis con resultados ambiguos.…”
Section: La Participación Y Sus Representaciones Socialesunclassified
See 1 more Smart Citation
“…En Estados Unidos, Neblo et al (2010) observan la existencia de profundas actitudes prodeliberativas entre los americanos frente a la tradicional participación electoral. En Europa, sin embargo, diversos trabajos han explorado esta tesis con resultados ambiguos.…”
Section: La Participación Y Sus Representaciones Socialesunclassified
“…In the United States, Neblo et al (2010) observed the existence of deep pro-deliberative attitudes among Americans as opposed to traditional electoral participation. In Europe, however, various studies have explored this thesis with ambiguous results.…”
Section: Bibliografíamentioning
confidence: 99%
“…Thompson 2008). In an influential article published in this journal, for instance, Michael Neblo and his colleagues test the hypothesis that "disaffection with modern mass democracy" stems mostly from "feelings of disempowerment and disillusionment" by relying on both survey data and extensive qualitative interviews concerning the "separability" of preferences for participation from different kinds of judgments concerning the state of contemporary politics (Neblo et al 2010). This leads them to draw the following three main conclusions:…”
Section: Is Deliberation Really An Incentive?mentioning
confidence: 99%
“…It is only with the interaction of these factors that a truly major problem emerges. And, even then, if public officials and members of the public can find a way to distinguish between rigged deliberation and high-quality forums, then the problem becomes much less acute (Neblo et al 2010).…”
Section: The Paradox Of Protecting Against Manipulationmentioning
confidence: 99%